Desfiles do cotidiano em ruas de São Paulo e Milão: a moda e os jogos de aparências na construção identitária - Clemente, Mariana Braga (2020)
This research explores the ways in which people show themselves to the world when walking through certain cities’ streets, the “daily walkways”. It is where game of visibilities is imperative, outlining practices that are here called “daily catwalks”. The question is to understand, by in loco observations, how such displays allow the construction of an identity, through the games of visibility and interactions, both between those who parade and between them and the city in which they circulate in. The streets of commerce and consumption of Fashion, with its propositions of ways of consuming products and sociability, loci of these interactions, consist of our research object. The main goal is to find, in the various mechanisms of construction of the subject’s appearance, the processes and dynamics of individual and collective identity construction that take place between continuities and discontinuities. Starting from a contextualization of the places called Fashion Quadrilaterals, a typology is elaborated. From that, two places were selected: Oscar Freire Street and adjacencies in São Paulo, Brazil; and Brera Street and surroundings in Milan, Italy. The corpus consists of 1110 photographs taken from the observations, which were described and analyzed, establishing global invariants (white sneakers and t-shirts) and local ones (skinny pants in São Paulo, and straight pants in Milan). The research uses as its theoretical-methodological tool the semiotics of A. J. Greimas and its developments, such as those elaborated by J-M. Floch, A.C. de Oliveira, E. Landowski, F. Marsciani, P. Violi, G. Ceriani, among others. It is concluded that these Quadrilaterals present themselves as spaces of belonging (and non-belonging) encompassed by the simulacrum of cosmopolitanism, and that Fashion, as an intersemiotic translation between languages, is also a form of (re)elaboration of the cultural memory that paces the social scenarios. In this context, the dynamics of the tastes of Fashion in the appearance games are due both by strategic interactions, and by melee interactions, spreading through contagion. The subjects who parade through these Quadrilaterals are mainly configured as Fashion followers, and in this sense, Fashion becomes a global normalizing instance of tastes. However, the constructed appearance articulates variations that not only evidence the local but are outlined as minimal gestures, as small escapes that individualize the presentations. This dynamic conceives the subjects individually and collectively and, between being and appearing the simulacrums of identities and otherness that architect the social interactions mediated by resemblances are built